‘Fortress Europe’: Compliance of the Dublin II Regulation with the European Convention for the Protection of Human Rights and Fundamental Freedoms - Lenart, Joanna (Utrecht Journal of International and European Law, 2012)
Recently, the Dublin II Regulation, a cornerstone of the emerging Common European Asylum System, has been gravely criticised, especially in context of the living conditions and general situation of asylum seekers in Greece. The main concerns regard the potential noncompliance of the Dublin II Regulation with the European Convention on Human Rights ('ECHR'), particularly with Article 3 - the prohibition of torture or inhuman or degrading treatment. This article examines the competing views in this respect. It analyses the relationship between EU law and the ECHR, protection of rights of refugees under the 1951 Convention relating to the Status of Refugees and main deficiencies of the Dublin II Regulation. The analysis starts with the non-equivalent protection of asylum seekers throughout the EU and finishes with the very limited definition of a family member and case law relevant to the principle of non-refoulement. This article concludes that the Dublin II Regulation per se cannot be deemed noncompliant with the ECHR. However, it emphasises the urgent need to change relevant legal provisions, or at least enforcement, and proposes possible solutions therein.